Creation Leumo Lon Sayang, Sayang Na Leumo Dance as a Criticism of Aceh Besar Regent Regulation No.5/2021 - Cufara, Dwindy Putri; Permata, Magfhirah Murni Bintang (Gondang: Jurnal Seni dan Budaya, 2023)
Public order is an ideal that can create calm, comfort and tranquility in people's lives. However, this is still far from being felt by the people of Jantho City, Aceh Besar Regency. This is due to the large number of livestock roaming around in public places such as residential areas, offices, parks, roads, etc. The rise in cases such as accidents, crop destruction and environmental pollution caused by animal waste needs to be a cause for concern. The regional government through Aceh Besar Regent Regulation No.5/2021 concerning Procedures for Controlling Livestock in Aceh Besar Regency has made efforts to prevent and resolve the above problems. In fact, until now the government seems to have turned a blind eye to what is happening in public. This needs to be a common concern in order to create order in livestock that is oriented towards orderly community life. This phenomenon is interesting to actualize in the form of a dance work entitled "Leumo Lon Sayang, Sayang Na Leumo". The aim of this research is to create a dance as criticism regarding Aceh Besar Regent Regulation No.5/2021. The method used in this research is Alma Hawkins method which consists of exploration, improvisation and forming. <w